Arterial hypertension and lifestyles in patients at the 24 de Mayo Health Center, Sucre canton - Escudero, Ana I.; Macías, Jesús V.; Párraga, María T.; Vélez, María J.; Bermello, Mercy E.; Bermello, William A. (Revista Gregoriana de Ciencias de la Salud, 2024)
Lifestyles are personal behaviors that can improve health or produce risks to deteriorate it. High blood pressure (HTN) is a chronic non-communicable disease, currently considered a public health problem, whose origins are multifaceted and is associated with unhealthy habits and risk factors. The objective of this work was to estimate the prevalence of HTN in patients at the 24 de Mayo Health Center (Sucre, Manabí, Ecuador) in relation to lifestyles. A descriptive, observational cross-sectional study was carried out from May to August 2023. The study revealed a prevalence of HTN of 4.81% in a sample of 8360 inhabitants, with a higher incidence observed in women and in the age group of 61 to 70 years old. Furthermore, 16.38% of the respondents also suffer from diabetes mellitus, indicating the need for a comprehensive approach in the management of these diseases. A close relationship was found between unhealthy lifestyles and HTN, underscoring the importance of implementing educational and public health interventions to promote healthier habits and reduce the prevalence of HTN in this community.